Developmental dynamics of mitochondrial fission and fusion proteins in functionally divergent skeletal muscles of goat - Sunil Pani; Unmod Senapati; Benudhara Pati; Bijayashree Sahu; Gourabamani Swalsingh; Punyadhara Pani; Subhasmita Rout; K. Gopinath Achary; Naresh C. Bal (Physiological Reports, 2024)
Abstract During skeletal muscle development, the intricate mitochondrial network formation relies on continuous fission and fusion. This process in larger mammals differs from rodents, the most used animal models. However, the expression pattern of proteins regulating mitochondrial dynamics in developing skeletal muscle remains unexplored in larger mammals. Therefore, we characterized the cellular expression and tissue‐level distribution of these proteins during development taking goat as a model. We have performed histological and immunohistochemical analyses to study metabolic features in various muscles. Neonatal muscles display uniform distribution of mitochondrial activity. In contrast, adult muscles exhibit clear distinctions based on their function, whether dedicated for posture maintenance or facilitating locomotion. Mitochondrial fission proteins like DRP‐1, MFF, and fusion proteins like MFN‐1 and 2 are abundantly expressed in neonatal muscles. Fission proteins exhibit drastic downregulation with limited peripheral expression, whereas fusion proteins continue to express in a fiber‐specific manner during adulthood. Locomotory muscles exhibit different fibers based on mitochondrial activity and peripheralization with high SDH activity. The proximity ligation assay between MFN1 and MFN2 demonstrates that their interaction is restricted to subsarcolemmal mitochondria in adult fibers while distributed evenly in neonatal fibers. These differences between postural and locomotory muscles suggest their physiological and metabolic properties are different.